2017
DOI: 10.18869/acadpub.hnmj.27.2.75
|View full text |Cite
|
Sign up to set email alerts
|

The Assessment of Fatigue and its Related Factors in Patients with Cancer

Abstract: Introduction: Cancer is a major health issue in Iran and in the rest of the world. Fatigue is one of the most complex and the most prevalent cancer-related problems that can affect various aspects of life for cancer patients. It can cause numerous problems. Objective: The aim of this study was to determine the level of fatigue and its associated factors in patients with cancer. Materials and Methods: In this descriptive-analytical study, 90 cancer patients referred to the oncology department in one of the teac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
2
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 7 publications
1
4
2
1
Order By: Relevance
“… 10 , 12 This study indicated that a higher stage of cancer shows high scores of fatigue, which is comparable with meta-analysis conducted in women breast cancer survivors with stage III cancer and treated with chemotherapy who were at a higher risk for severe fatigue than survivors with stage I cancer. 31 The present study showed the prevalence of fatigue among types of cancer such as cervical and breast cancer is consistent with the study result reported in India that the most prevalent fatigue was cervical cancer (28.6%), followed by breast cancer. 32 Clinical factors like infection have been seen as causative elements in fatigue and that was identified in this study and it is consistent with the study results reported from the Netherlands of increased risk for severe fatigue following cancer treatment.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“… 10 , 12 This study indicated that a higher stage of cancer shows high scores of fatigue, which is comparable with meta-analysis conducted in women breast cancer survivors with stage III cancer and treated with chemotherapy who were at a higher risk for severe fatigue than survivors with stage I cancer. 31 The present study showed the prevalence of fatigue among types of cancer such as cervical and breast cancer is consistent with the study result reported in India that the most prevalent fatigue was cervical cancer (28.6%), followed by breast cancer. 32 Clinical factors like infection have been seen as causative elements in fatigue and that was identified in this study and it is consistent with the study results reported from the Netherlands of increased risk for severe fatigue following cancer treatment.…”
Section: Discussionsupporting
confidence: 92%
“…This study showed that fatigue in patients who had received radiation therapy is similar to the prevalence of fatigue among patients receiving radiotherapy reported in the UK but lower than the result found in Rasht teaching hospital. 31 …”
Section: Discussionmentioning
confidence: 99%
“…In some other studies, the prevalence of fatigue in patients undergoing treatment was equivalent to our study. 8 , 9 The differences between the results of fatigue rate in these studies and the current study may be due to cultural differences. While our study was conducted in Tabriz with a Turkish culture, the studies by Sharifi Rizi et al, 8 and Zeighami Mohammadi et al, 9 had been conducted in Isfahan and Tehran, respectively, with a Persian culture.…”
Section: Discussioncontrasting
confidence: 61%
“… 5 - 7 In a study by Sharifi Rizi et al, 59% of cancer patients under treatment reported significant levels of fatigue. 8 Another study by Zeighami Mohammadi et al, reported that 95% of Iranian cancer patients suffer from fatigue. 9 CRF is a distressing, persistent, and subjective sense of physical, emotional, and/or cognitive tiredness related to cancer or cancer treatment, that is not proportional to recent physical activity and interferes with the patient’s functioning.…”
Section: Introductionmentioning
confidence: 99%
“…Inclusion criteria were the patients aged 18 -65 years, men and women with various types of cancer (22) undergoing routine periodic chemotherapy, the absence of skeletal and muscular problems and anomalies, lack of a history of cardiovascular diseases (23), lack of exercise during the study period (22,24), spending at least one course of chemotherapy for each patient before the study (22,25), ability to perform the basic and daily activities (26), total white blood cell (WBC) count of above 3,000 in each session of complete blood count, the platelet count of above 50,000, and hemoglobin level of above 8g/dL (27), normal vital signs in each period, the lack of chemotherapy and radiotherapy at the same time, patients residing in Ahvaz and its suburbs. Exclusion criteria were transferring the patient to the ICU ward and holding the chemotherapy, transferring the patient to another treatment center to continue treatment, and the patient's death.…”
Section: Participant Eligibilitymentioning
confidence: 99%